2018
DOI: 10.1186/s40479-018-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

A psychoeducational group intervention for family and friends of youth with borderline personality disorder features: protocol for a randomised controlled trial

Abstract: BackgroundCaring for a person with borderline personality disorder is associated with poor outcomes including elevated psychological distress and burden. This study will compare the effectiveness of two brief psychoeducational programs for carers of youth presenting for early intervention for borderline personality disorder features. The protocol for this study is presented here.MethodsThe study is a single-centre parallel group, randomised controlled trial. As a family unit, relatives, partners and friends (‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…They found that carers reported reduced subjective, but not objective, burden and increased personality disorder knowledge at the completion of a three session cognitive analytic therapy-informed program called 'Making Sense of BPD'. The findings have led to a randomised controlled trial evaluation of the program [38]. Future studies are needed to examine the effects of increasing adaptive coping skills on carer and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that carers reported reduced subjective, but not objective, burden and increased personality disorder knowledge at the completion of a three session cognitive analytic therapy-informed program called 'Making Sense of BPD'. The findings have led to a randomised controlled trial evaluation of the program [38]. Future studies are needed to examine the effects of increasing adaptive coping skills on carer and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Data for both BPD groups were collected at baseline, as part of a randomised controlled trial evaluating psychoeducation interventions for carers of yp-BPD [ 38 ]. Consecutive sampling was employed to reduce sampling bias [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early intervention for young people with BPD, including support for carers, is designed to prevent or reduce the severity of long‐term problems with social functioning (Chanen et al, 2017). Members of our group have developed and evaluated the only intervention programs specifically for carers of young people with BPD features: the face‐to‐face MS‐BPD psychoeducation group program (Pearce et al, 2017) and two Online modules, Introduction to Early Intervention for Borderline Personality Disorder and Caring For a Young Person with Borderline Personality Disorder ‐ Information for Families and Friends (Betts et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Families and friends of an individual with BPD experience high levels of psychological symptoms, including anxiety and depression, objective and subjective burdens, and grief. [19] Moreover, family members experience negative feelings, despair, sadness and regret, humiliation, guilt, and shame towards their relatives diagnosed with BPD. [8] Family roles and relationships become strained due to the emotional challenges of having a sibling with BPD.…”
Section: Discussionmentioning
confidence: 99%